LA INTERRUPCIÓN DEL RÉGIMEN DE VISITAS Y VULNERACION DE DERECHOS FUNDAMENTALES. LIMA SUR 2020 - Reynoso Mujica, Mayra Alejandra (2020)
The thesis revolves around a behavior that previously appeared isolated and that today has become frequent, such as the interruption of the visitation regime, which is a phenomenon that has been incorporated into the legislation of family law and rights. children and adolescents, although not yet in its full dimension, because there is no express regulation of such conduct, despite causing serious damage against the fundamental rights of children and adolescents and also of the father or mother who is prevents you from visiting your child. Hence, the title of our investigation is: “The interruption of the visitation regime and violation of fundamental rights. South Lima. 2020 ”. The research does not intend to describe the phenomenon, but rather through a study of the legislation and the reality of what happens in the Lima Sur judiciary, to propose a new legislative proposal that addresses the issue in its entirety. Posing as the main problem the following question: In what way does the interruption of the visitation regime affect the violation of fundamental rights from the perspective of the operators and lawyers of the North Lima judiciary in the year 2021? and as a general objective: it is to determine how the interruption of the visitation regime affects the violation of fundamental rights from the perspective of the operators and lawyers of the North Lima judiciary in the year 2021. Regarding the Methodology, it has been used a quantitative approach, the descriptive type of study. The research level is basic-descriptive, cross-sectional (transactional). It uses the technique of surveying professionals such as lawyers and operators of the family judiciary who are knowledgeable about the problem. Keywords: Interruption, obstruction, visitation, violation of fundamental rights.